Experimental assessment of the behavior of expanded glass lightweight reinforced concrete walls. (15th May 2022) - Lombardi, R.; Jünemann, R.; Lopez, M.
Abstract: Structural lightweight concrete (LWC) can significantly reduce the dead loads of reinforced concrete (RC) structures and therefore the associated seismic forces. A new LWC was made using expanded glass as lightweight aggregate (LWA), which is comparatively much lighter than conventional LWAs, and might lead to different performance in lightweight RC elements. An experimental study was conducted to evaluate the structural behavior of expanded glass LWC RC walls. Two types of RC walls were built and tested under cyclic displacement protocol: slender confined and squat unconfined walls. For each type of wall, four specimens were considered: two with LWCs with f c ′ of 30 and 40 MPa (i.e., L30 and L40) and densities of 1200 and 1700 kg/m 3, respectively; and two with normal weight concretes (NWC) with the same specified strengths acting as control specimens (i.e., N30 and N40) and a density of about 2400 kg/m 3 . These walls were analyzed in terms of yield drifts and strengths, maximum drifts and strengths, ductility and energy dissipation. Results show that slender confined walls made with L30 mixture showed reductions in ductility and energy dissipation of about 56 and 34%, respectively when compared to N30 specimens. Meanwhile, L40 specimens showed the same tendency, but with smaller reductions compared to N40 of about 36% of ductility and 10% of energy dissipation. In squat unconfined walls, a significant reduction of strength was observed for both types of LWCs, although a bigger difference was observed in L30 concrete. Overall, expanded glass LWC showed promising structural behavior, especially L40 mixture, which presented relatively small differences compared to its NWC counterpart and had only 70% of its unit weight. Highlights: The behavior of wall specimens made with lightweight and normal concrete was studied. Expanded glass lightweight concrete shows promising structural behavior. Lightweight concrete walls showed similar performance to normal-weight concrete walls.